Assisi in silence - Sbicca, Arturo; Rich, Clive; Oriente Occidente Productions; Soundview Media Partners ([Assisi, Italy] : Oriente Occidente Productions, 2002)
Chronicles the hidden network by the clergy of Assisi that saved persecuted Jews during WWII.
Originally released as a motion picture in 2002.
Narrator: Clive Rich.
Cinematographer, Massimo Santopaolo ; editor, AXIS multimedia.
In English, German, Italian with English subtitles for non-English dialogues. Also available in Italian, with English and Italian subtitles for non-Italian dialogues.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 20, 2019)
Keywords: Holocaust, Jewish (1939-1945) -- Italy; World War, 1939-1945 -- Jews -- Rescue -- Italy -- Assisi; Assisi (Italy); Documentary films; Short films; Nonfiction films; Internet videos; Streaming video